Suitability of Mycorrhiza-Defective Rice and Its Progenitor for Studies on the Control of Nitrogen Loss in Paddy Fields via Arbuscular Mycorrhiza - Zhang, Shujuan; You, Zhaoyang; Guo, Xinyue; Yun, Wenfei; Xia, Yu; Rillig, Matthias C. (Frontiers in Microbiology, 2020)
Employing mycorrhiza-defective mutants and their progenitors does not require inoculation or elimination of the resident microbial community in the experimental study of mycorrhizal soil ecology. We aimed to examine the suitability of mycorrhiza-defective rice (non-mycorrhizal, Oryza sativa L., cv. Nipponbare) and its progenitor (mycorrhizal) for research aboutto evaluate nitrogen (N) loss control from paddy fields via arbuscular mycorrhizal (AM) fungi. We grew these two rice lines in soils with the full community of AM fungi and investigated root AM colonization. In the absence of AM fungi, we estimated rice N content, soil N concentration and microbial community on the basis ofbased on phospholipid fatty acids; we also quantified N loss via NH3 volatilization, N2O emission, runoff and leaching. In the presence of With AM fungi, we did not find any evidence of AM colonization for non-mycorrhizal rice while mycorrhizal rice was colonized and percentage of root colonization was 17% - 24%. In the absence of soil without AM fungi, these two rice lines had similar N content, soil N concentration and microbial community. Importantly, there was no significant difference in N loss via all the four pathways between mycorrhizal and non-mycorrhizal systems. This mycorrhizal/non-mycorrhizal rice pair is suitable for further research on the role of AM fungi in the control of soil N loss control from in paddy fields.